2013
DOI: 10.1007/s10903-013-9855-z
|View full text |Cite
|
Sign up to set email alerts
|

HPV Awareness and Vaccine Acceptability in Hispanic Women Living Along the US-Mexico Border

Abstract: Despite advances in prevention of cervical cancer in the US, women of Hispanic origin still bear an unequal burden in cervical cancer incidence, morbidity and mortality. Our objective was to determine the HPV vaccine knowledge and acceptability in a group of mostly Hispanic females. In this cross sectional survey, 62 % of participants heard of HPV; 34.9 % identified HPV as a cause of cervical cancer. 63 % of participants reported willingness to receive vaccine and 77 % were willing to vaccinate daughters. Thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The low knowledge scores in our findings are consistent with results of previous studies of HPV knowledge within various subsets of the Latino population (Bair, Mays, Sturm, & Zimet, 2008; Kepka et al, 2012; Kepka et al, 2015; Molokwu et al, 2014). We found similar scores compared to the results of the Gerend et al (2013) study of knowledge among Latina mothers at a Federally Qualified Health Center in Florida.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The low knowledge scores in our findings are consistent with results of previous studies of HPV knowledge within various subsets of the Latino population (Bair, Mays, Sturm, & Zimet, 2008; Kepka et al, 2012; Kepka et al, 2015; Molokwu et al, 2014). We found similar scores compared to the results of the Gerend et al (2013) study of knowledge among Latina mothers at a Federally Qualified Health Center in Florida.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is important to understand farmworkers’ knowledge of HPV in order to develop interventions that will increase vaccine uptake and mitigate health disparities. Previous research has also documented low levels of HPV knowledge among other Latino communities in the United States (Galbraith et al, 2016; Gerend et al, 2013; Kepka et al, 2012; Kepka, Warner, Kinney, Spigarelli, & Mooney, 2015; Luque et al, 2010; Luque et al, 2015; Molokwu, Fernandez, & Martin, 2014; Reimer, Schommer, Houlihan, & Gerrard, 2014). Several studies have found that knowledge of HPV among parents in Mexico is also low (Lazcano-Ponce et al, 2001; Moraros et al, 2006; Wentzell et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Eighty percent of those who had heard about vaccination stated they would consider getting vaccinated themselves, and 87% would recommend it to relatives and friends. The acceptability of HPV vaccination among the women in our UAE sample is similar to that reported in other studies from developed countries with established HPV vaccination programs (Haesebaert et al, 2012;Molokwu et al, 2013), and much higher than the acceptability rates reported from less developed countries (Bair et al, 2008;Phan et al, 2012). Our study also shows that the acceptability of HPV vaccination in the UAE is better than in other Islamic countries such as Turkey, where acceptability ranges between 12% (Durusoy et al, 2010) and 44% (Kilic et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Knowledge about HPV and HPV vaccine tends to be modest among Hispanic adults (12-17), though most Hispanic parents are willing to vaccinate their adolescent daughters (17-21). Recent data suggest that HPV vaccine initiation (receipt of at least one dose) may be higher among Hispanic adolescent females compared to non-Hispanic whites (8), though Hispanics may be less likely to complete the three-dose series after receiving the first dose (8, 22).…”
Section: Introductionmentioning
confidence: 99%